Early Childhood Education according to Abdurrahman An-Nahlawi and Maria Montessori - Aghnaita, Aghnaita; Maemonah, Maemonah (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2020)
This research is motivated by the concept of Early Childhood Education offered by various educational figures to impact the emergence of increasingly dynamic educational theories. Issues on this concept did not escape the attention of Abdurrahman An-Nahlawi and Maria Montessori. The two figures have similarities and differences in their underlying points of view and approaches, and these cannot be separated from the philosophical study behind them. Based on the above, this study explores the two figures’ thoughts to give birth to a new paradigm of education for early childhood. The research method used was a literature study by collecting various references that can support research. From the research results, it can be found that, philosophically, the concept of Early Childhood Education, according to Abdurrahman An-Nahlawi, is attached to the perennial normative approach, while Maria Montessori’s notion is more towards a constructivism approach. The two approaches have different points of view in highlighting the educational side. The similarity in the points of view of these two figures is an understanding of the concept of education, which should be integrated and contextual, and position the child as the main subject in education.